-9-3x=-24-6x

Simple and best practice solution for -9-3x=-24-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9-3x=-24-6x equation:



-9-3x=-24-6x
We move all terms to the left:
-9-3x-(-24-6x)=0
We add all the numbers together, and all the variables
-3x-(-6x-24)-9=0
We get rid of parentheses
-3x+6x+24-9=0
We add all the numbers together, and all the variables
3x+15=0
We move all terms containing x to the left, all other terms to the right
3x=-15
x=-15/3
x=-5

See similar equations:

| 20-4e=6 | | 748=r+574 | | 8x+9(x-32.500)=557.500 | | 7x-14-3x=8x-7 | | x+10(-7+6)=2(x+6)+2 | | -7(x+4)=-56 | | 8(9x+7)-3x=-6 | | -6(w+2)=7w+14 | | 2/3x-1/3x=-14/15 | | 529=23p | | 6x-2(x-3)=4(x+1)+5 | | -7v+19=2(v-4) | | 430=10q | | 6+12z-4=7z+3+4 | | 2(x-5)-4x=2 | | 2x+3=6x+13+3x | | 6-x/2=7 | | 3x-17=-68 | | 3x+10+x-30=360 | | x-9=(x-2) | | 2x+1/9+x=90 | | 3x+16=15x-5 | | z+38=92 | | 33=p-18 | | 3x+10(−2x+2)=3/2​(10x−4)+5 | | 15x2+29x=14 | | x(×)=40 | | 10x-54=x+63 | | 5+x/9=1 | | 19x+16x-17=-17x | | .16a+21=a | | 9×-(3x-10)=64 |

Equations solver categories